2005
DOI: 10.1029/2005jd006004
|View full text |Cite
|
Sign up to set email alerts
|

Chamber studies of secondary organic aerosol growth by reactive uptake of simple carbonyl compounds

Abstract: [1] Recent experimental evidence indicates that heterogeneous chemical reactions play an important role in the gas-particle partitioning of organic compounds, contributing to the formation and growth of secondary organic aerosol in the atmosphere. Here we present laboratory chamber studies of the reactive uptake of simple carbonyl species (formaldehyde, octanal, trans,trans-2,4-hexadienal, glyoxal, methylglyoxal, 2,3-butanedione, 2,4-pentanedione, glutaraldehyde, and hydroxyacetone) onto inorganic aerosol. Gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
517
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 355 publications
(567 citation statements)
references
References 74 publications
42
517
6
Order By: Relevance
“…α-Dicarbonyls showed concentrations ranging from 3.5 to 289 ng m -3 , with an arithmetical average of 51.5 ng m -3 in daytime and 59.8 ng m -3 in nighttime. Glyoxal (Gly) and methylglyoxal (MeGly) are gas-phase oxidation products of numerous VOCs such as benzene, toluene, xylene (Volkamer et al, 2001), ethylene (Ervens et al, 2004), isoprene (Zimmermann and Poppe, 1996) and terpene (Fick et al, 2004), and could act as precursors of secondary organic aerosols via heterogeneous processes (Kroll et al, 2005;Liggio et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…α-Dicarbonyls showed concentrations ranging from 3.5 to 289 ng m -3 , with an arithmetical average of 51.5 ng m -3 in daytime and 59.8 ng m -3 in nighttime. Glyoxal (Gly) and methylglyoxal (MeGly) are gas-phase oxidation products of numerous VOCs such as benzene, toluene, xylene (Volkamer et al, 2001), ethylene (Ervens et al, 2004), isoprene (Zimmermann and Poppe, 1996) and terpene (Fick et al, 2004), and could act as precursors of secondary organic aerosols via heterogeneous processes (Kroll et al, 2005;Liggio et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…HCHO oligomerization is also proposed to contribute to the partitioning of gaseous HCHO to aerosol phase (Toda et al, 2014). But, during a chamber study, Kroll et al (2005) did not find any growth of both neutral ((NH 4 ) 2 SO 4 ) and acidic (NH 4 HSO 4 ) aerosols in the presence of gaseous HCHO, suggesting that the uptake of HCHO by aerosols is unlikely taking place. Although numerical simulations of HCHO, either by multi-dimensional models or box models, can in some cases reproduce HCHO observations (Wagner et al, 2001;Fried et al, 2003b;MacDonald et al, 2012), significant discrepancies between modeled and measured HCHO concentration have been frequently found (Choi et al, 2010;Fried et al, 2011, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…As first indicated by Volkamer et al (2007), if loss of CHOCHO on aerosol surfaces is not taken into account, models can substantially overestimate measured CHOCHO concentrations. Laboratory studies found that uptake of CHOCHO by aerosols is mainly through polymerization process and is related with the acidity and the ionic strength within the aqueous phase of aerosols (Jang and Kamens, 2001;Liggio et al, 2005;Kroll et al, 2005). Once CHOCHO is taken up by aerosols, it can contribute to the formation of secondary organic aerosols (Volkamer et al, 2007;Tan et al, 2009;Washenfelder et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] (HCO) 2 is the simplest -dicarbonyl and its atmospheric significance stems from its role in aerosol formation, [8][9][10] and use as a marker of biogenic emission. 11,12 In addition, (HCO) 2 photochemistry is a recognised source of HOx (OH and HO 2 ) radicals in the troposphere.…”
Section: Introductionmentioning
confidence: 99%